The relationship between deferred imitation, associative memory, and communication in 14-months-old children. Behavioral and electrophysiological indices - Nordqvist, Emelie; Rudner, Mary; Johansson, Mikael; Lindgren, Magnus; Heimann, Mikael (Frontiers in Psychology, 2015)
The present study combines behavioral observations of memory (deferred imitation after a brief delay of 30 minutes and after a long delay of 2-3 weeks) and electrophysiological (Event-Related Potentials, ERP) measures of associative memory as well as parental reports of nonverbal and verbal communication in sixteen 14-months-old children. Results show that for deferred imitation, the children remembered the stimulus after the brief but not after the long delay. There was a clear electrophysiological response indicating associative memory. Furthermore, a correlation between deferred imitation and ERP suggests that both measures of memory (deferred imitation and associative memory) tap into similar mechanisms in 14-months-old prelingual children. There was also a statistically significant relation between parental report of receptive (verbal) language and the ERP, showing an association between receptive language skills and associative memory in 14-months-old children.